Cerebral Blood Perfusion after Treatment with Zolpidem and Flumazenil in the Baboon - Clauss, Ralf P.; Dormehl, Irene C.; Kilian, Elmaré; Louw, Werner K.A.; Nel, Wally H.; Oliver, Douglas W. (Arzneimittelforschung, 2002)
Previous studies have shown that zolpidem (CAS 82626-48-0) can lead to improved perfusion in damaged brain tissue. Zolpidem belongs to the imidazopyridine chemical class and it illicits its pharmacological action via the γ-aminobutyric acid (GABA) receptor system through stimulation of particularly the ω1 receptors and to a lesser extent ω2 receptors. Previously it was reported that no cerebral blood flow effects were observed in normal baboons after treatment with zolpidem, whereas an asymmetric regional increase in cerebral blood flow was observed in a neurologically abnormal baboon. In this study, the effect of a combination of the benzodiazepine receptor antagonist flumazenil (CAS 78755-81-4) and zolpidem on brain perfusion was examined by the 99mTchexamethyl-propylene amine oxime (99mTc-HMPAO) split dose brain single photon emission computed tomography (SPECT). Four normal baboons and the neurologically abnormal baboon from the previous zolpidem study were examined. In the current study the asymmetric changes observed after zolpidem-only treatment in the abnormal baboon was attenuated by flumazenil intervention. A decreased brain blood flow was observed after combination treatment of zolpidem and flumazenil in the normal baboons. The involvement of the omega receptors is suggested by these results. Upor down-regulation of omega receptors may also contribute to the observed responses in the abnormal baboon and a brain injured patient.
Keywords: CAS 78755-81-4; CAS 82626-48-0; Flumazenil, baboon, combination with zolpidem, effect on cerebral blood perfusion; Omega receptors; Zolpidem, baboon, combination with flumazenil, effect on cerebral blood perfusion